The effects of an empowerment program to have a good quality of life and long life for elderly people in Phrae Province, Thailand - Somsak Thojampa; Laddawan Daengthern; Kittisak Kumpeera (Elsevier, 2020)
This is a quasi-experimental research project that aims to study the effects of an Empowerment Program for elderly people to have a good quality of life and long life, by comparing the perception of a good quality of life and health behaviors among elderly people 60 years old and older who live in Phrae Province. There are 30 samples in the control group and 30 samples in the experiment group. The result reveals, as follows: 1) the average score of the quality of life and health behaviors after the experiment are higher than their previous scores before the experiment among the elderly people in the experiment group that participated in the Empowerment Program, 2) the average scores of the quality of life and health behaviors between elderly people in the experiment group and the control group, compared after the experiment group participated in the Empowerment Program, are different which have a statistical significance (p-value <0.05). The elderly people that participated in the Empowerment Program have higher average scores of quality of life and health behaviors.